Recursive model and unique code (pattern) generation for authentication and authorization in grid computing - Najhan Muhamad Ibrahim (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2009)
Security requirements are fundamental to the grid design and architecture. The basic security components within the Grid environment provide the mechanisms for authentication, authorization, and confidentiality of communication between grid computers. Some of the security models generate simple security codes where they would be easy to be cracked and some have applied bio-metric generations. Biometric model will lead to future privacy issue where most nations have approved to use data protection act, where some action or misuse of this Bio-metric data will be construed as conducting a crime with or without intention. This research explores biobased recursive programming theory to serve the best security mechanism for future Grid Computing where currently the security issues of Computer Grid environment are still at its infancy stage, an area with very high potential to conduct research. The main motivation for this project is to explore whether bio-based recursive programming model will be able to generate a promising Authentication and Authorization code patterns. The Tower of Hanoi is the meta-magical model where it is able to be modified to adapt to generate bio-like genetic codes and such few research study of similar nature has successfully been conducted. In this research study we generated and evaluated unique codes or patterns which would be with particles of large and randomized codes that are non-repetitive and non-predictive strings of genetic codes. In this modified model by using combinations of recursive models with step-wise randomization, each generated pattern will deliver different authentication or authorization certificates. We are also able to compare which other recursive models that would generate the most effective code or pattern to be used as authentication or authorization certificates. Programming recursive code generator using multiple Towers of Hanoi was implemented on the Grid computing environment that itself had generated the unique code or the unique pattern to obtain the required authentication and authorization certificates.